Comparative Evaluation of Functional and Aesthetic Outcomes in Reconstruction of Commissure of Mouth with Radial Forearm Free Flap with and without Palmaris Longus Tendon in Patients being Operated for Squamous Cell Carcinoma of Buccal Mucosa and Lip: A Research Protocol - Imran Saleem Solanki; Rajanikanth Kambala; Nitin Bhola (Journal of Clinical and Diagnostic Research)
Introduction: Previously conducted studies have demonstrated the effectiveness of the Radial Forearm Flap (RFF) in reconstructing lip and buccal mucosa deformities, both with and without the Palmaris Longus Tendon. The optimal therapy following large oncologic resections involves microvascular free flaps. The tissue produced by the Radial Forearm Free Flap (RFFF) is thin, malleable and well-vascularised, ensuring less morbidity at the donor site since it is harvested based on the radial artery. Successful vascularisation is facilitated by microvascular anastomosis. With a high success rate, RFFF provides good functional and cosmetic results for a range of intraoral reconstructions. Need of the study: This study aims to evaluate the functional and aesthetic results of reconstructing the lip and buccal mucosa in cases of Squamous Cell Carcinoma (SCC). The long-term preservation of vertical lip height and lip support is achieved by the Palmaris Longus Tendon, which functions as a sling over which the flap is elevated. Aim: To compare and evaluate functional and aesthetic outcomes in the reconstruction of the commissure of the mouth using RFFF, with and without the Palmaris Longus tendon, in patients undergoing surgery for SCC of the buccal mucosa and lip. Materials and Methods: This parallel group randomised trial will be conducted at the Department of Oral and Maxillofacial Surgery, Siddharth Gupta Memorial Cancer Hospital, Datta Meghe Institute of Higher Education and Research, Sawangi, Wardha, Maharashtra, India from August 2024 to September 2025. The procedure will be performed on patients who have histopathologically confirmed Oral Squamous Cell Carcinoma (OSCC). Detailed case histories, clinical examinations, past medical and dental histories, general personal information and biopsy procedures will be conducted. Patients with biopsy-proven SCC will then undergo radiographic examinations (CT scans) to determine the extent of the lesion and lymph node metastasis. Patients with biopsy confirmation who meet the inclusion criteria will be included in the study after obtaining detailed informed consent. The study will consist of two groups of eight patients each: one group will receive RFFF with the Palmaris Longus tendon and the other will receive RFFF without the Palmaris Longus tendon. Functional outcomes such as drooling, swallowing and speech, along with aesthetic outcomes including smile, lip competence and commissural ends, will be assessed.